Analisis Perlindungan Hukum Terhadap Nasabah Bank Dalam Penggunaan Internet Banking - Kamila, Zulfa; Apriani, Rani (Peneliti.net, 2024)
Web banking is a help for managing banking exchanges by means of the web or on the web. However, due to the ease with which transactions can be conducted, it is not uncommon for criminals to exploit these technological advancements, which clearly have the potential to harm Internet Banking customers. This study utilizes a regularizing juridical strategy with a regulation methodology or a juridical methodology. It very well may be presumed that the lawful assurance for clients utilizing web banking administrations given by the bank as far as innovation security is maximal. The best legitimate assurance is contained in the